(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
The experiment was conducted in the Boro season of 2016-17, at Bangladesh Rice Research Institute (BRRI) farm under the Agro Ecological Zone (AEZ 28) Modhupur Tract. CN6 is a high spikelet bearing early maturing advanced line of rice but low in spikelet fertility. Supplemented nutrient management was examined to increase its spikelet fertility. Five treatments were used in this experiment. The treatments were as follows: T1 = BRRI recommended fertilizer dose + MgO @ 0.05%, T2 = BRRI recommended fertilizer dose + 60 g MoP + 60 g elemental S (80% wp) + 20 g ZnSO4, T3 = BRRI recommended fertilizer dose + Boron @ 5 ppm, T4 = BRRI recommended fertilizer dose + Copper @ 5 ppm) and T5 = BRRI recommended fertilizer dose alone. The experiment was conducted in Randomized Complete Block design with three replications. The results revealed that Treatment T3 (BRRI recommended fertilizer dose + Boron @ 5ppm) produced the more number of grains per panicle with an average of 201 which is 19.9% higher number of grains per panicle over the BRRI recommended fertilization under the treatment of T5. However, higher grain yield were recorded in treatment T3 compare to the control treatment T5 (BRRI recommended fertilization). Taken together, our results suggested that BRRI recommended fertilization alone with supplemented nutrient management, especially boron, significantly increased the spikelet fertility of the CN6 advanced line of Boro rice resulting higher yield. Res. Agric., Livest. Fish.7(1): 17-23, April 2020